Video pulse conversion into a radio frequency pulsed waveform of complex composition - Karelin, S.Y.; Krasovitsky, V.B.; Lebedenko, A.N.; Magda, I.I.; Mukhin, V.S.; Sinitsin, V.G.; Volovenko, N.V. (Вопросы атомной науки и техники, 2022)
The paper is a feasibility study for a nonlinear wave guiding structure, based on a coaxial line with a magnetized ferrite core inside, to form broadband pulsed signals with a controllable radio-frequency spectrum. A set of two serially connected coaxial guides of different diameters of order 10¹ mm is analyzed, where the ferromagnetic is subjected to an axial magnetizing field and the azimuthal field belonging to the initially incident video pulse. Possibilities have been demonstrated for a targeted alteration, over a broad band like Δf/f = 0.25…0.55, of the waveform and gigahertz-range frequency spectrum of the output signal. In case of employing a feeding high-voltage signal of relatively short duration it may become possible to implement the Peak Power Amplification operating mode.